The importance of law and ethics in achieving a holistic medical education for muslim medical professionals - Jahn Kassim, Puteri Nemie; Osman, Ariff; Wan Muhammad, Ramizah (2016)
The changing landscape in medical care has created greater rights and responsibilities for the medical professionals. As patient autonomy is given pre-eminence in majority of medical decision-making, medical paternalism has undesirably been pushed to the backseat. Medical professionals can no longer decide what is best for their patients. Instead, they need to understand the new horizon in which law and ethics play a vital role in determining the boundaries of rightful conducts that has been determined for the medical profession. Thus, it is imperative that they are educated on the knowledge of medical law and ethics and integrate it in their daily practice. Particularly for Muslim medical professionals, they need to conform to the Islamic core values that constantly promote the ideals of professionalism which include dedication, respect, compassion, empathy, honesty, altruism, responsibility, integrity, self-improvement, magnanimity and accountability. In achieving this, rigorous applications of behavioural and ethical standards need to be developed over a period of training at the early stage of the medical career. Medical students should be educated to develop attributes of medical professionalism during their undergraduate education at the University. The importance of their responsibilities as medical professionals should also be imbued through a holistic medical education process combining lectures and workshop discussion of case studies that relates to the needs of the society and the demands of law, religion and ethics. Consequently, the outcome of this process will guide future Muslim medical professionals to execute their duties with greater accountability and within the realms of acceptable legal rulings. This will promote safer medical practice for the benefit of the society and ultimately, be in conformity with the demands of the Maqasid al Shariáh.